(untitled) (Research, Society and Development, 2021)
This work was aimed at to perform the characterization qualitative and quantitative of the bacterial groups responsible for the oxidation and nitrogen reduction processes, applying the most likely number (NMP) technique in an experimental system consisting of UASB reactor, Percolator Biological Filter (FBP) and anoxic reactor, installed and monitored sequentially in the process of leachate treatment from landfill and domestic sewage. The efficiency of the ammonification stage observed during the conversion phase from organic to inorganic nitrogen in the UASB reactor was 6.4%, representing an increase of 9.8 mg/L of ammoniacal nitrogen in the effluent of the reactor. The NMP of ammonia oxidizing bacteria (AOB) ranged from 0,8x102 a 1,4x105 NMP/100ml. The NMP of nitrite oxidizers (NOB), varied from 0,8x102 a 2,2x104 NMP/100ml. For denitrifying bacteria, the NMP ranged from 7,0x103 a 2,6x104 NMP/100ml. The removal biological nitrogen ammoniacal observed in the FBP showed an average efficiency of 16.42%, generating an effluent with an average concentration of 136.4 mg NH4+.L-1 in the FBP. Based on these results, the system experimental demonstrated the ability to carry out global nitrogen transformation processes. However, the need for strict control over operational parameters is highlighted, in order to achieve greater efficiencies in nitrogen removal in the long run.